PERFORMA PERTUMBUHAN IKAN SELUANG ASAL PULAU BANGKA (Brevibora dorsiocellata) DENGAN PEMBERIAN PAKAN BERBEDA DALAM WADAH BUDIDAYA PADA SKALA LABORATORIUM DI TAHAP AWAL DOMESTIKASI - Zambawi, Muhammad; Syarif, Ahmad Fahrul; Robin, Robin (JURNAL PERIKANAN TROPIS, 2020)
This research aimed to evaluated the growth performance of eyespot rasbora (Brevibora dorsiocellata) feeding with different feed in cultured conditions on early stage of domestication. The fishes was collected from river among Balunijuk Village, Bangka Residence. It’s conducted on February until March 2019 at  Laboratory of Aquaculture Sub-Laboratory of Hatchery, University of Bangka Belitung. A kinds of feed on this tretment was blood worms (Tubificidae) and commercial feed (pellet). The parameters observed in this research was surival rates, absolute weight and length and feed consumptions level. The result showed that the survival value ranged on 90-100%., the absolute weight was 0,12±0,02 until 0,17±0,02 grams, the absolute length was 0,69±0,17 until 0,79±0,06 cm and a feed consumptions level was 10±0,58 until 11±1,00 gram. In common, the eyespot rasbora (Brevibora dorsiocellata) showed the postively responses on early stage of domestications with different feed on cultured medium.Keywords : Bangka Island, Brevibora dosrsiocellata, Domestication, Eyespot Rasbora